2017
DOI: 10.1002/sys.21412
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative methods for engineering systems: Why we need them and how to use them

Abstract: This paper discusses the role that qualitative methods can and should play in engineering systems research and lays out the process of doing good qualitative research. As engineering research increasingly focuses on sociotechnical systems, in which human behavior and organizational context play important roles in system behavior, there is an increasing need for the insights qualitative research can provide. This paper synthesizes the literature on qualitative methods and lessons from the authors’ experience em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
(98 reference statements)
0
40
0
Order By: Relevance
“…Setting up the experiment in this way, lets researchers observe the nature of that interaction and its impact on solution quality directly, but it also forces the team to employ more nuanced observational tools similar to those used traditionally in more qualitative studies. 52 As a result, internal validity is derived from the depth of our observation. This is an appropriate tradeoff given the relative immaturity of our understanding of the phenomenon and the limited opportunity for empirical observation.…”
Section: Natural Field Experiments Can Balance Contextual Richness Wimentioning
confidence: 97%
See 1 more Smart Citation
“…Setting up the experiment in this way, lets researchers observe the nature of that interaction and its impact on solution quality directly, but it also forces the team to employ more nuanced observational tools similar to those used traditionally in more qualitative studies. 52 As a result, internal validity is derived from the depth of our observation. This is an appropriate tradeoff given the relative immaturity of our understanding of the phenomenon and the limited opportunity for empirical observation.…”
Section: Natural Field Experiments Can Balance Contextual Richness Wimentioning
confidence: 97%
“…This is a conscious experimental design choice—the interaction among capability and complexity is critical theoretically and in practice. Setting up the experiment in this way, lets researchers observe the nature of that interaction and its impact on solution quality directly, but it also forces the team to employ more nuanced observational tools similar to those used traditionally in more qualitative studies . As a result, internal validity is derived from the depth of our observation.…”
Section: Examples Of Experiments In Systems Engineering and Design (Smentioning
confidence: 99%
“…In order to gain an in‐depth understanding of how oversight impacts engineering work at the contractor level, we used qualitative research methods . Since it has been suggested that previously measured categories of oversight‐related activities are incomplete, there is a need to inductively develop a comprehensive perspective of the categories of work performed for oversight‐related purposes .…”
Section: Research Approachmentioning
confidence: 99%
“…Thus, qualitative methods aim to produce theories whereas quantitative methods aim to test theories’ predictions. An excellent overview of qualitative methods is given in this special issue …”
Section: Relationship To Other Standards Of Rigormentioning
confidence: 99%
“…An excellent overview of qualitative methods is given in this special issue. 93 Not all hypothesis generation techniques are qualitative. Indeed, from the perspective of predictive theorizing, axiomatic methods also constitute a source of causal theories that can be tested to determine if they correspond to empirical findings.…”
Section: Relationship To Hypothesis Generation Techniquesmentioning
confidence: 99%